Medicaid expansion in Oregon and postpartum healthcare among people with and without prenatal substance use disorder - Haight, Sarah C.; Yoon, Jangho; Luck, Jeff; Harvey, Marie; Shapiro-Mendoza, Carrie; Li, Rui; Ko, Jean Y. (Drug and alcohol dependence reports, 2022)
•Associations between Medicaid expansion and Medicaid-financed postpartum healthcare differed by SUD.•Medicaid expansion not associated with increased Medicaid-financed postpartum care in people with SUD.•Medicaid expansion associated with increased Medicaid-financed postpartum care in people without SUD.•For OUD, Medicaid expansion associated with increased Medicaid-financed OUD-related medications. People with a maternal substance use disorder (SUD) may experience a lack of access to necessary healthcare and more specifically, postpartum healthcare. It is not known whether increased insurance coverage introduced by Medicaid expansion has improved postpartum healthcare utilization among this population. Oregon 2008–2016 birth certificates and Medicaid claims were used to examine whether continuous insurance enrollment and postpartum healthcare utilization increased post-Medicaid expansion in a population with and without SUD (n = 9,337). International Classification of Diseases codes were used to identify deliveries, SUD, and postpartum healthcare. Univariable and multivariable generalized linear regression with standard errors clustered by individual were used to estimate the association between Medicaid expansion and postpartum healthcare utilization, stratified by maternal SUD. Among the 10.3% with SUD, expansion was not associated with increased continuous enrollment or postpartum healthcare utilization. Among those without SUD, post-expansion deliveries were associated with increased continuous enrollment (+105.0 days; 95% CI=96.9–113.2), total (+4.4; 95% CI=2.9–6.0), postpartum (+0.3; 95% CI=0.2–0.4), inpatient (+0.9; 95% CI=0.7–1.1), outpatient (+2.3; 95% CI=1.4–3.3), office (+0.9; 95% CI=0.2–1.6), and emergency department (+0.3; 95% CI=0.1–0.5) visits. Among deliveries to postpartum people with SUD, 27.2% had opioid use disorder (OUD); expansion was associated with increased OUD medication use (12.0% vs 18.3%) and number of fills (6.7 vs 16.6). Medicaid expansion in Oregon was only associated with increased Medicaid-financed healthcare utilization for postpartum people without SUD, with the exception of those with OUD, demonstrating the need for assessing various strategies to improve postpartum healthcare utilization.